Conversión Alimenticia en Cuyes Blancos en Etapa de Crecimiento con una Tercera Progenie de Cruce Genético de tipo Absorbente - Sulca Toapanta, Jenny Paola (2017)
This research was carried out at the Experimental and Production Center Salache (CEYPSA) to determine the feed conversion in white guinea pigs at the stage of growth with a third progeny. The objectives of this study were the identification of animals, the grouping of males and females, data collection to determine the feed conversion using records for weekly weights of guinea pigs, the weight of food offered and daily residue, it was performed a comparative analysis with the two previous progenies to evaluate the improved animals. The researcher worked with 15 guinea pigs, seven females and eight males. The identification of the white ones with plastic earrings with their respective coding was performed, the guinea pigs were weighed once a week to obtain initial weight and final weight, the weight of the animal was taken to know the amount of feed to be offered Which was obtained with 30% of live weight and after its consumption was weighed the residue, with which the food consumption was acquired. For the results of the general weight gain an analysis of the test of t was applied, determining the average of 440 g, in the general food consumption determines the average of 1579.85 g, in the general feed conversion is 3.66, concluding that their p-values determine that there is statistical difference in the three parameters. Finally the correlation between progenies, 1 and 3 was performed, its correlation coefficient is -0.1 determined to be negative and null, whereas the correlation coefficient of progenies 2 and 3 is 0.46 determining that it is positive but weak.